GYNECOLOGICAL STATUS OF PATIENTS WITH COLORECTAL CANCER - V. A. Solodky; U. Stanoevich; I. V. Stanoevich; I. A. Zelenina; V. D. Chikvadze (Сибирский онкологический журнал)
The purpose of the study was to identify risk factors for colorectal cancer on the basis of retrospective analysis of gynecological history and status of 183 patients with colon adenocarcinoma treated at the Russian X-Ray Radiology Research Center between 1996 and 2011. Evaluation of gynecological status was based on findings  of gynecological, transvaginal and ultrasound examinations of the genitals, as well as on cytological cervical screening and colposcopy. Hysteroscopy and separate diagnostic curettage were performed if necessary. Gynecological status of patients with colorectal cancer was characterized by ovarian hypofunction and high incidence of benign non-inflammatory (78.1 %) and inflammatory (88.0 %) disorders of genital tract. In most cases (63.9 %) polyneoplasia in patients with colorectal cancer combined with breast, endometrial and ovarian cancers. Considering younger age of the onset of benign disease of the genital tract, this group of patients should be followed up carefully for the development of colon cancer.